A perspective on implantable biomedical materials and devices for diagnostic applications. (June 2021) - Pulugu, Priyanka; Ghosh, Sumanta; Rokade, Shital; Choudhury, Kaushik; Arya, Neha; Kumar, Prasoon
Abstract: New sensors, sensing schemes, and sensor materials have revolutionized the field of personalized diagnostics. Functional, biocompatible, and flexible materials have spearheaded the development of various wearable and implantable sensors over the last decade. The present-day sensors may be integrated into the patient's body and monitor the desired physiological parameters in real time. This has been achieved by hybrid biomaterials that exhibit enhanced electrical, mechanical, magnetic, and chemical properties when compared with the conventional biomaterials. These materials are developed through surface modification and doping with nanomaterials, rendering them amenable for any biosensor development. These sensors are also capable of seamlessly transmitting the acquired data to specific recipients using advanced electronics. In this article, we have presented a review of some of the recent advancements in the domains of neural, cardiovascular, metabolic, and musculoskeletal sensor systems, which have seen significant developments in the recent times.